Relationship between Some Trace Elements, Lipid profile and Hypothyroidism - Nada Faisal Rashid; Baydaa Ahmed Abed; Thaer Arhayl Abas (College of Pharmacy / Mustansiriyah University, 2010)
There are many questions still remain concerning the relationship between the trace elements and thyroid hormones. Therefore, this study was undertaken to evaluate the concentration levels of some trace elements (zinc, copper, selenium, manganese, magnesium), and to reach the possible correlation between these trace elements and thyroid hormones in hypothyroidism. The study was included 50 patients with hypothyroidism and 28 healthy volunteers' serves as control group matched with age, sex, and body mass index (BMI). All participant had not taken vitamin or mineral supplements for at least 2 weeks before sampling, blood sampling were drawn to determine the serum trace elements levels (Zn, Cu, Se, Mn, and Mg), thyroid hormone (T3, T4, and TSH), and lipid profile (TC, TG, LDL, HDL, and VLDL). The results indicate that the hypothyroidism patients have significant increase in TSH levels (P< 0.01), and significant decrease in T3, T3/T4 levels (P<0.001), although, there were decrease in serum trace elements (Se, Zn, Cu, Mn, and Mg) in hypothyroidism patients compared with controls group, (P< 0.001 for all serum Se, Zn, Cu, Mn, and P< 0.01 for Mg). The results indicate that there was no significant correlation between serum Cu, Mn, Mg and T3, T4, and TSH level; but, there was a significant positive correlation between Se-T3 (r=0.286, P<0.04), and Zn-T3 (r=0.3, P<0.01), also there was only a significant negative correlation between serum Se-TSH levels (r=-0.315, P< 0.02) in hypothyroidism patients. There is significant increase in the mean serum cholesterol (TC), triglycerides (TG), and low density lipoprotein (LDL) in patients compared with normal controls (P 0.01, P<0.001, <0.05) respectively. Also, there is significant decrease in the mean serum concentration of high density lipoprotein (HDL) in the patients with hypothyroidism than control, and our results showed that there is positive correlation between TSH levels and lipid (cholesterol, triglyceride, and very low density lipoproteins), although, there is negative correlation between Mg concentration and lipid (TC, TG, LDL) levels. We conclude that the trace elements Se, Zn, Cu, Mn, and Mg have altered in hypothyroidism patients; there are correlations between some trace elements (Se, and Zn) and thyroid hormones, but there are no obvious correlations between the other trace elements (Cu, Mn, and Mg) status and thyroid hormones. That is means there is an interactions between some trace elements and thyroid hormones levels.